A THOUSAND GODS OF HATTIAN LAND - Tülin CENGİZ (Fırat University, 2019)
B.J. Collins is right about the religion when he says “it is an element refreshing every direction of Hatti life”. As “the deities”, “religious practices (rituals)” and mythological elements are examined, it is conceived that religion isn’t only a mental attitude about supernatural beings and powers, but also a system relating with Hittite socio-political structure and its imperialist politics. As the Hittite state expanded from its core in central Anatolia, the range of gods mentioned in the royal archives came to include deties that were worshiped in the urban centers of Syria and Mesopotamia as well as those Indo-European and Hattic origin. In the earliest period, the Hattic deties of cult centers such as Nerik and Hattuša predominated, later to be joined by increasing, numbers of newcomers at home in region to the south and east. Embracing these gods with no self pantheon indicates the existence of a tolerance culture. However, given that the tolerance is a paradoxicconcept in itself, thatthisparadox is based on the inequality between the “tolerating” and the “tolerated”, and that the idea of “dominance” by the “tolerating” overthe “tolerated” lies at theroot of this inequality, it can be said that there is not an emotional norethereal purposelying behind the expression “ThousandGods of theHattian Land”, but rather it is an earthlyone. In Hittites, as one of theprominent figures of Antic world, where the politics and religion are directed with economy, the change and expansion of its pantheon to coincide with the history of the Kingdom as whole and complete comprises the main subject of this study.